The Claremont Report on Database Research. - AGRAWAL, RAKESH; AILAMAKI, ANASTASIA; BERNSTEIN, PHILIP A.; BREWER, ERIC A.; CAREY, MICHAEL J.; CHAUDHURI, SURAJIT; DOAN, ANHAI; FLORESCU, DANIELA; FRANKLIN, MICHAEL J.; GARCIA-MOLINA, HECTOR; GEHRKE, JOHANNES; GRUENWALD, LE; et al. (Communications of the ACM, 2009)
The article discusses a gathering of computer architects, database researchers, and computer users which met in May 2008 to examine the state of database research and the effects such research is having on actual practice. A consensus was reached that, due to both the explosion of data and usage scenarios, as well as shifts seen in computing hardware and platforms, the database community was at a major turning point. Topics include future directions of database research, database engine architectures, and declarative programming languages.